Effects of Green Technology on Firms’ Profitability and Solvency: A Study on Textiles Industry of Bangladesh - Uddin, Nazim; Miah, Musa (Asian Business Review, 2020)
In recent years there has been increasing advocacy regarding the perception that turning green is good for the corporation and thus for the whole economy. Green technology is nowadays a popular term in any industry but the stakeholders always ask a question of whether the company benefits from using green technology or is there any financial gain? This question remains unanswered in our country, and because of that new entities are not willing to adopt green technology especially in the textile sector. This paper shows that the companies using green technology having financial benefits than the companies not using green technology. In this paper, we used financial performance measurement techniques to find out companies’ financial health. This study has taken data of 43 listed companies of Dhaka Stock Exchange. Then it divides the data into two groups, a group accustomed to green technology and a group not accustomed to green technology. Firstly, we used profitability ratios (ROS, ROA, ROE) to find out two groups of companies’ position. Profitability ratios vary significantly from one group to another. Secondly, we used solvency ratios (Debt asset ratio and debt-equity ratio) and find result almost similar but the result changes with the passages of time through the payment of installment. So from the study, it can be said that profitability is positively related to the adoption of green technology. Thus, by studying this paper company will be keen to adopt green technology in their organization. This paper will also help existing companies to improve the existing technology.